MENINGKATKAN HASIL BELAJAR KONSEP HIDROLISIS GARAM MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TAI (TEAM ACCELERATED INSTRUCTION)PADA SISWA KELAS XI IPA 3 SMA NEGERI 1 LIMBOTO - Salam, Siti Nurhaida AR; Lukum, Astin; Paputungan, Mardjan (Jurnal Entropi, 2009)
This research is an Action Classrom Research that is held in SMAN I Limboto at Even Semester, 2008/2009 Academic Years. The subject of research is class XI IPA 3 which have 28 students that consist of 9 boys and 19 girls. The object of thisreserch is to increase the students achievement by using Type TAI (Tiem Accelerated Instruction) Cooperative Learning Style. This researchheld in 2 cycles that research is 85 % Student get up to 70 and the learning activities which are marked by using observation sheet minimally reach good category. The students achievement on the first cycle shows the classical absorptive power reaches 89,55% and the study completeness reaches 96.43% This achievement show that the usage of type TAI (Team Accelerated Instruction) Cooparative Learning Style could increase the Students Achievement.